Preparation method of V-MOF nano material and application of V-MOF nano material in aqueous zinc battery

By using 2-bromoterephthalic acid and hydrothermal reaction technology in the synthesis of V-MOF materials, sea urchin-like V-MOF nanomaterials were prepared, which solved the problem of insufficient structural stability and conductivity, and significantly improved its performance and synthesis efficiency in aqueous zinc batteries.

CN119798700APending Publication Date: 2025-04-11YANGZHOU UNIV

Patent Information

Application Number
CN202510060649.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

V-MOF materials face challenges in practical applications in terms of structural stability and conductivity, which affects their performance in aqueous zinc batteries.

Method used

By using 2-bromoterephthalic acid as an organic ligand and synthesizing sea urchin-like V-MOF nanomaterial under ultrasonic and hydrothermal reaction conditions, the crystal structure and specific surface area are adjusted and its electrochemical properties are improved.

Benefits of technology

The conductivity, charge storage capacity and cycle stability of V-MOF materials are improved, making their performance in aqueous zinc ion batteries better than the V-MOF synthesized by the prior art, and the synthesis yield is increased to 85%, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798700A_ABST
    Figure CN119798700A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a V-MOF nano material, which comprises the following steps: dissolving vanadium salt in absolute ethyl alcohol to form a solution A, and dissolving organic ligands 2-bromoterephthalic acid and diluted hydrochloric acid in absolute ethyl alcohol to form an organic ligand solution B; mixing the solution A and the organic ligand solution B, and performing stirring reaction to obtain a mixed solution C; reacting the mixed solution C under an ultrasonic condition to obtain a mixed solution D; the mixed solution D is subjected to a constant-temperature hydrothermal reaction, and after the hydrothermal reaction is finished, a product is cleaned to obtain the V-MOF nano material. According to the application of the V-MOF nano material in the aqueous zinc battery, the V-MOF nano material is prepared into electrode slurry, the surface of a titanium foil is coated with the electrode slurry, and the electrode slurry is dried to serve as an electrode plate of the aqueous zinc battery. The prepared vanadium-based nano material has high conductivity and cycling stability, the electrochemical performance of the aqueous zinc battery can be improved, the preparation process is simple and easy to operate, and the sea urchin-shaped V-MOF nano material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of V-MOF and application thereof, belonging to the technical field of electrode materials. Background Art

[0002] Metal organic frameworks (MOFs) are a common type of porous crystalline materials. Since their discovery, they have attracted more and more attention due to their high porosity, diverse structures, rich varieties, and controllable morphology. They are different from inorganic porous materials and general organic complexes, and have the rigidity of inorganic materials and the flexibility of organic materials. Moreover, due to the ability to control the pore structure and large specific surface area, MOFs have a wider range of application prospects than other porous materials, such as gas separation, catalysts, and energy storage materials.

[0003] Vanadium-based metal-organic framework (V-MOF) materials have significant advantages in aqueous zinc batteries. Vanadium has high electrochemical activity and can provide good charge storage capacity in battery reactions. V-MOF materials can optimize electronic conductivity and ion transport paths by adjusting the coordination of their metal center (vanadium) and organic ligands, further improving the energy density and cycle stability of the battery. However, V-MOF materials still face some problems in practical applications, especially the structural stability and conductivity of the materials. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing a V-MOF nanomaterial, the purpose of which is to improve the conductivity of the electrode and the cycle stability of the battery. The present invention also provides an application of the V-MOF nanomaterial in an aqueous zinc battery.

[0005] The technical solution of the present invention is as follows: A method for preparing a V-MOF nanomaterial comprises the following steps:

[0006] Dissolving vanadium salt in anhydrous ethanol to form solution A, dissolving organic ligand 2-bromoterephthalic acid and dilute hydrochloric acid in anhydrous ethanol to form organic ligand solution B;

[0007] The solution A and the organic ligand solution B are mixed and stirred to react to obtain a mixed solution C;

[0008] The mixed solution C is reacted under ultrasonic conditions to obtain a mixed solution D;

[0009] The mixed solution D is subjected to a constant temperature hydrothermal reaction, and after the hydrothermal reaction is completed, the product is washed to obtain a V-MOF nanomaterial.

[0010] Furthermore, the temperature of the constant temperature hydrothermal reaction is 140-170° C., preferably 150-160° C., and the time of the constant temperature hydrothermal reaction is 40-50 hours.

[0011] Furthermore, the vanadium salt is VCl 3. In the actual preparation process, VCl 3 is used, because chloride ions are easily removed, and it is easier to obtain the desired product.

[0012] Furthermore, the molar ratio of the vanadium salt, the organic ligand 2-bromoterephthalic acid and the hydrochloric acid is (1-2):(1-2):2.

[0013] Furthermore, during the stirring reaction, the stirring speed is not less than 400 r / min, and the stirring reaction time is 40 to 50 min.

[0014] Furthermore, the ultrasonic frequency of the reaction under the ultrasonic condition is 80 to 120 Hz, and the reaction time is 15 to 25 minutes.

[0015] Furthermore, the temperature during the reaction under ultrasonic conditions is 20-30°C.

[0016] Another technical solution of the present invention is as follows: an application of a V-MOF nanomaterial in an aqueous zinc battery, wherein the V-MOF nanomaterial prepared by the preparation method of the V-MOF nanomaterial is made into an electrode slurry and coated on the surface of a titanium foil, and then used as an electrode sheet of an aqueous zinc battery after drying.

[0017] Furthermore, the electrode slurry made of the V-MOF nanomaterial includes an electrode material and a slurry solvent, wherein the electrode material includes 70% to 75% by mass of the V-MOF nanomaterial, 15% to 20% of conductive carbon black Super P, and the rest is a binder.

[0018] Compared with the prior art, the advantages of the technical solution provided by the present invention are:

[0019] The present invention uses 2-bromoterephthalic acid as an organic ligand to replace the terephthalic acid used in the prior art. By introducing bromine, the crystal structure of V-MOF is adjusted, different functional groups are provided, the structural characteristics of the material in the synthesis process are improved, and the electrochemical properties of V-MOF are improved. Combined with the control of the hydrothermal reaction temperature, a sea urchin-shaped V-MOF nanomaterial can be obtained, which has a larger specific surface area, better ion transmission channels and higher stability.

[0020] The performance of sea urchin-shaped V-MOF in aqueous zinc-ion batteries is better than that of V-MOF synthesized by prior art, with a specific capacity of up to 113.8 mAh / g at a current density of 1000 mA / g. The material obtained by the method of the present invention has better conductivity, charge storage capacity and cycle stability, making it more advantageous in applications such as energy storage and electrochemical catalysis.

[0021] The synthesis yield of the present invention is increased to 85%, side reactions are reduced, and more precursor materials are ensured to be converted into the target product V-MOF.

[0022] The invention has simple operation, easy reaction control, good repeatability and safety, and is suitable for continuous large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD spectrum of the V-MOF nanomaterial of Example 1.

[0024] Figure 2 This is the FT-IR spectrum of the V-MOF nanomaterial of Example 1.

[0025] Figure 3 This is the SEM spectrum of the V-MOF nanomaterial of Example 1 (magnified 5000 times).

[0026] Figure 4 This is the SEM spectrum of the V-MOF nanomaterial of Example 1 (magnified 10,000 times).

[0027] Figure 5 This is a CV curve graph of a battery prepared using the V-MOF nanomaterial of Example 1 as the positive electrode material.

[0028] Figure 6 Cyclic stability spectrum of the battery prepared with the V-MOF nanomaterial of Example 1 as the positive electrode material DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading this description, various equivalent modifications to this description by those skilled in the art fall within the scope defined by the claims attached to this application.

[0030] Example 1

[0031] (1) Weigh 2 mmol of 2-bromoterephthalic acid (C8H4Br2O4) and 2 ml of 2 mol / L dilute hydrochloric acid and dissolve them in 5 mL of anhydrous ethanol solution to form an organic ligand solution B.

[0032] (2) Weigh 2 mmol of vanadium trichloride (VCl3) and put it into 5 mL of anhydrous ethanol solution, and obtain a brown turbid solution A by using a magnetic stirrer.

[0033] (3) The organic ligand solution B obtained in step (1) is added to the solution A obtained in step (2) while stirring, and the mixture is stirred at a speed of 550 r / min using a magnetic stirrer for 50 min to obtain a mixed solution C.

[0034] (4) The mixed solution C obtained in step (3) was placed in an ultrasonic cleaner and subjected to ultrasonic treatment at an ultrasonic frequency of 100 Hz and a temperature of 25° C. for 20 min to obtain a mixed solution D.

[0035] (5) The mixed solution D obtained in step (4) was transferred to a polytetrafluoroethylene stainless steel reactor and heated to 160° C. for a constant temperature hydrothermal reaction for 48 h.

[0036] (6) The precipitate obtained in step (5) was washed with anhydrous ethanol and then dried in a vacuum oven for 12 h to obtain a sea urchin-shaped V-MOF nanomaterial.

[0037] Example 2

[0038] (1) Weigh 1.5 mmol of 2-bromoterephthalic acid (C8H4Br2O4) and 2 ml of 2 mol / L dilute hydrochloric acid and dissolve them in 5 mL of anhydrous ethanol solution to form an organic ligand solution B.

[0039] (2) Weigh 1.5 mmol of vanadium trichloride (VCl3) and put it into 5 mL of anhydrous ethanol solution, and use a magnetic stirrer to obtain a brown turbid solution A.

[0040] (3) The organic ligand solution B obtained in step (1) is added to the solution A obtained in step (2) while stirring, and the mixture is stirred at a speed of 500 r / min using a magnetic stirrer for 45 min to obtain a mixed solution C.

[0041] (4) The mixed solution C obtained in step (3) was placed in an ultrasonic cleaner and subjected to ultrasonic treatment at an ultrasonic frequency of 120 Hz and a temperature of 20° C. for 25 min to obtain a mixed solution D.

[0042] (5) The mixed solution D obtained in step (4) was transferred to a polytetrafluoroethylene stainless steel reactor and heated to 160° C. for a constant temperature hydrothermal reaction for 48 h.

[0043] (6) The precipitate obtained in step (5) was washed with anhydrous ethanol and then dried in a vacuum oven for 12 h to obtain a sea urchin-shaped V-MOF nanomaterial.

[0044] Example 3

[0045] (1) Weigh 1 mmol of 2-bromoterephthalic acid (C8H4Br2O4) and 2 ml of 2 mol / L dilute hydrochloric acid and dissolve them in 5 mL of anhydrous ethanol solution to form an organic ligand solution B.

[0046] (2) Weigh 1 mmol of vanadium trichloride (VCl3) and put it into 5 mL of anhydrous ethanol solution, and obtain a brown turbid solution A by using a magnetic stirrer.

[0047] (3) The organic ligand solution B obtained in step (1) is added to the solution A obtained in step (2) while stirring, and the mixture is stirred at a speed of 450 r / min using a magnetic stirrer for 40 min to obtain a mixed solution C.

[0048] (4) The mixed solution C obtained in step (3) was placed in an ultrasonic cleaner and subjected to ultrasonic treatment at an ultrasonic frequency of 80 Hz and a temperature of 30° C. for 15 min to obtain a mixed solution D.

[0049] (5) The mixed solution D obtained in step (4) was transferred to a polytetrafluoroethylene stainless steel reactor and heated to 160° C. for a constant temperature hydrothermal reaction for 48 h.

[0050] (6) The precipitate obtained in step (5) was washed with anhydrous ethanol and then dried in a vacuum oven for 12 h to obtain a sea urchin-shaped V-MOF nanomaterial.

[0051] Example 4

[0052] In step (5), the mixture is heated to 140° C. and a constant temperature hydrothermal reaction is carried out for 50 h. The remaining steps are the same as those in Example 1, thereby obtaining a sea urchin-shaped V-MOF nanomaterial.

[0053] Example 5

[0054] In step (5), the mixture is heated to 150° C. and a constant temperature hydrothermal reaction is carried out for 45 hours. The remaining steps are the same as those in Example 1, thereby obtaining a sea urchin-shaped V-MOF nanomaterial.

[0055] Example 6

[0056] In step (5), the mixture is heated to 170° C. and a constant temperature hydrothermal reaction is carried out for 40 hours. The remaining steps are the same as those in Example 1, thereby obtaining a sea urchin-shaped V-MOF nanomaterial.

[0057] Example 7

[0058] In step (2), 2 mmol of vanadyl sulfate (VOSO4·nH2O) was weighed and added to 5 mL of anhydrous ethanol solution, and a brown turbid solution A was obtained by a magnetic stirrer. The remaining steps were the same as in Example 1 to obtain a sea urchin-shaped V-MOF nanomaterial.

[0059] The product prepared in Example 1 was characterized by X-ray powder diffraction (XRD) test, and the diffraction pattern of the product was obtained as follows: Figure 1 As shown, the diffraction peaks at 8.32°, 12.08°, 16.58°, 25.00°, 27.20°, 32.04°, and 42.16° indicate that V-MOF nanomaterials were prepared in Example 1, and V-MOF nanomaterials were also prepared in the remaining examples.

[0060] In addition, the functional groups of the V-MOF nanomaterial prepared in Example 1 were characterized by FT-IR test. The results are as follows Figure 2 As shown, at 1708cm -1 、1552cm -1 、1400cm -1 and 761cm -1 The absorption peaks at the positions are respectively attributed to ν(C=O), ν(C=C), δ(OH) and ν(OVO), further confirming that V-MOF nanomaterials were prepared in Example 1.

[0061] The morphology of the V-MOF nanomaterial prepared in Example 1 was characterized by SEM testing. Figure 3 and Figure 4 The scanning electron microscope pictures of the V-MOF nanomaterial prepared in Example 1 at magnifications of 5000 and 10000 times are shown respectively. The test results show that the V-MOF nanomaterial prepared in Example 1 has a sea urchin-like morphology, and its size and shape are basically uniform.

[0062] It should also be noted that, in addition to using vanadium trichloride (VCl3) to prepare solution A, vanadium salts such as vanadyl sulfate (VOSO4·nH2O) can also be used to prepare solution A. The remaining steps are the same as those in Example 1, and sea urchin-shaped V-MOF nanomaterials can be prepared. The yield of each example is above 80%, and the yield of Example 1 reaches 85%.

[0063] Comparative Example 1

[0064] (1) Weigh 2 mmol of vanadium oxysulfide (VOSO4·nH2O) and 2 mmol of terephthalic acid and dissolve them in 20 mL of N,N-dimethylformamide solution to form a mixed solution A.

[0065] (2) The mixed solution A was stirred at 550 r / min by a magnetic stirrer for 30 min.

[0066] (3) The mixed solution A was transferred to a polytetrafluoroethylene stainless steel reactor and heated to 160° C. for a constant temperature hydrothermal reaction for 72 h.

[0067] (4) The yellow-brown precipitate obtained in step (3) was washed with methanol and then dried in a vacuum oven at 80° C. for 24 h to obtain a layered V-MOF nanomaterial.

[0068] Comparative Example 2

[0069] (1) Weigh 2 mmol of terephthalic acid and 2 ml of 2 mol / L dilute hydrochloric acid and dissolve them in 5 mL of anhydrous ethanol solution to form an organic ligand solution B.

[0070] (2) Weigh 2 mmol of vanadium trichloride (VCl3) and put it into 5 mL of anhydrous ethanol solution, and obtain a brown turbid solution A by using a magnetic stirrer.

[0071] (3) The organic ligand solution B obtained in step (1) is added to the solution A obtained in step (2) while stirring, and the mixture is stirred at a speed of 550 r / min using a magnetic stirrer for 50 min to obtain a mixed solution C.

[0072] (4) The mixed solution C obtained in step (3) was placed in an ultrasonic cleaner and subjected to ultrasonic treatment at an ultrasonic frequency of 100 Hz and a temperature of 25° C. for 20 min to obtain a mixed solution D.

[0073] (5) The mixed solution D obtained in step (4) was transferred to a polytetrafluoroethylene stainless steel reactor and heated to 160° C. for a constant temperature hydrothermal reaction for 48 h.

[0074] (6) The precipitate obtained in step (5) was washed with anhydrous ethanol and then dried in a vacuum oven for 12 hours to obtain a spindle-shaped V-MOF nanomaterial. The yield of this comparative example was about 40%.

[0075] The V-MOF nanomaterials obtained in each embodiment and comparative example are used to assemble a battery, and the steps are as follows:

[0076] (1) Weigh 0.5 g of PVDF, add 9.5 g of NMP, and stir for 24 h to prepare PVDF with a mass fraction of 5%.

[0077] (2) Weigh 70 mg of V-MOF nanomaterial and 20 mg of Super P and grind them for 30 min.

[0078] (3) Weigh 200 mg of 5% PVDF, add it to step (2), and stir for 8 h to prepare an electrode slurry.

[0079] (4) Use a tetrahedral coater to evenly coat the electrode slurry prepared in step (3) on the surface of the titanium foil and keep it in a vacuum drying oven at 60° C. for 12 h.

[0080] (5) The electrode material prepared in step (4) was cut into electrode sheets using a 12 mm die.

[0081] (6) Prepare 3M Zn(CF3SO3)2 electrolyte.

[0082] (7) The electrode sheet of step (5) is used as the positive electrode, the zinc sheet is used as the negative electrode, the diaphragm is selected as a glass fiber diaphragm, and the electrolyte is 3MZn(CF3SO3)2. The button battery is assembled by traditional methods. The positive and negative electrodes are CR2032 stainless steel shells. The assembled battery is left to stand for 24 hours before further electrochemical performance testing.

[0083] The assembled battery was subjected to a CV curve test with a scan rate of 0.6 mV / s to obtain the redox potential of the electrode and analyze the electrochemical reaction occurring at a specific potential. Figure 5 The CV curve of the battery prepared by using the V-MOF of Example 1 as the positive electrode material. The redox peaks show that Zn 2+ Insertion / extraction.

[0084] The assembled battery was subjected to a cycle stability test with a current density of 1000 mA / g and 500 cycles to evaluate the battery performance. The cycle stability spectrum of the battery prepared with the V-MOF as the positive electrode material in Example 1 is shown in FIG. Figure 6 shown.

[0085] The results of each embodiment and comparative example are as follows

[0086]

[0087] From the above results, it can be seen that the method of the present invention can be used to prepare V-MOF nanomaterials that are approximately in the shape of a sea urchin, especially under the hydrothermal reaction temperature of 160°C, the prepared V-MOF nanomaterials have good morphology uniformity and have the best electrochemical properties.

Claims

1. A method for preparing a V-MOF nanomaterial, characterized in that: Includes steps: Dissolving vanadium salt in anhydrous ethanol to form solution A, dissolving organic ligand 2-bromoterephthalic acid and dilute hydrochloric acid in anhydrous ethanol to form organic ligand solution B; The solution A and the organic ligand solution B are mixed and stirred to react to obtain a mixed solution C; The mixed solution C is reacted under ultrasonic conditions to obtain a mixed solution D; The mixed solution D is subjected to a constant temperature hydrothermal reaction, and after the hydrothermal reaction is completed, the product is washed to obtain a V-MOF nanomaterial.

2. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The temperature of the constant temperature hydrothermal reaction is 140-170° C., and the time of the constant temperature hydrothermal reaction is 40-50 hours.

3. The method for preparing the V-MOF nanomaterial according to claim 2, characterized in that: The temperature during the constant temperature hydrothermal reaction is 150-160°C.

4. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The vanadium salt is VCl3.

5. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The molar ratio of the vanadium salt, the organic ligand 2-bromoterephthalic acid and the hydrochloric acid is (1-2):(1-2):

2.

6. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The stirring speed during the stirring reaction is not less than 400 r / min, and the stirring reaction time is 40 to 50 min.

7. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The ultrasonic frequency for the reaction under the ultrasonic condition is 80-120 Hz, and the reaction time is 15-25 min.

8. The method for preparing the V-MOF nanomaterial according to claim 1, characterized in that: The temperature during the reaction under the ultrasonic condition is 22-26°C.

9. Application of V-MOF nanomaterial in aqueous zinc battery, characterized in that: The V-MOF nanomaterial prepared by the preparation method of the V-MOF nanomaterial according to any one of claims 1 to 8 is made into an electrode slurry, coated on the surface of a titanium foil, and used as an electrode sheet of an aqueous zinc battery after drying.

10. The use of the V-MOF nanomaterial in an aqueous zinc battery according to claim 9, characterized in that: The electrode slurry made of the V-MOF nanomaterial comprises an electrode material and a slurry solvent. The electrode material comprises 70% to 75% by mass of the V-MOF nanomaterial, 15% to 20% of conductive carbon black Super P, and the rest is a binder.

Citation Information

Patent Citations

  • Novel vanadium-oxygen coordination supramolecular positive electrode material as well as preparation method and application thereof

    CN115010943A

  • Universal and rapid method for preparing MOFs (Metal-Organic Frameworks) material and continuous production equipment

    CN118027435A

  • Method for producing electrochemical fibrous adsorbent and electro-and variable electromagnetic adsorption method

    CN118450940A

  • Electrodes having electrode additive for high performance batteries and applications of same

    US20200185788A1

Cited By

  • Zinc negative electrode modified by telescopic gel interface layer as well as preparation method and application of zinc negative electrode

    CN121709515A

  • Preparation method of MOF-based anode interface modification layer as well as product and application of MOF-based anode interface modification layer

    CN122494538A